Integrated Business Model: Applying the St. Gallen Management Concept to Business Models - Doleski, Oliver D (Springer, 2015)
The St. Gallen Management Concept could be termed the DNA of the Integrated Business Model that is developed and detailed by Oliver D. Doleski. The practical St. Gallen Management Concept offers a good conceptual framework for the development of change, and increasingly dynamic change, which is now more than ever the key factor shaping business actions. The complexity arising from this very dynamism is becoming a defining characteristic of today’s markets. Traditional methods and business models can deliver less than ideal results in this difficult environment. New approaches to business development are needed. To master complexity, these approaches must fully integrate all of the many and diverse aspects and demands of normative, strategic and operational management.